2020
DOI: 10.1038/s41467-020-19822-6
|View full text |Cite
|
Sign up to set email alerts
|

A multivariable Mendelian randomization analysis investigating smoking and alcohol consumption in oral and oropharyngeal cancer

Abstract: The independent effects of smoking and alcohol in head and neck cancer are not clear, given the strong association between these risk factors. Their apparent synergistic effect reported in previous observational studies may also underestimate independent effects. Here we report multivariable Mendelian randomization performed in a two-sample approach using summary data on 6,034 oral/oropharyngeal cases and 6,585 controls from a recent genome-wide association study. Our results demonstrate strong evidence for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 50 publications
(82 reference statements)
3
58
0
Order By: Relevance
“…For oral and oropharyngeal cancer, an MR study using genetic data on 6000 oral or oropharyngeal cancer cases and 6600 controls found a positive causal effect of alcohol consumption independent of smoking [ 16 ]. The authors concluded that previous estimates of the association between alcohol and oral and oropharyngeal cancer from observational studies may have been underestimated [ 16 ].…”
Section: Alcohol and Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…For oral and oropharyngeal cancer, an MR study using genetic data on 6000 oral or oropharyngeal cancer cases and 6600 controls found a positive causal effect of alcohol consumption independent of smoking [ 16 ]. The authors concluded that previous estimates of the association between alcohol and oral and oropharyngeal cancer from observational studies may have been underestimated [ 16 ].…”
Section: Alcohol and Cancer Riskmentioning
confidence: 99%
“…For oral and oropharyngeal cancer, an MR study using genetic data on 6000 oral or oropharyngeal cancer cases and 6600 controls found a positive causal effect of alcohol consumption independent of smoking [ 16 ]. The authors concluded that previous estimates of the association between alcohol and oral and oropharyngeal cancer from observational studies may have been underestimated [ 16 ]. Another MR study on UK Biobank data found that drinking alcohol, especially above the UK’s low-risk guideline of up to 14 units per week, was causally related with head and neck cancers, but not breast cancer [ 17 ].…”
Section: Alcohol and Cancer Riskmentioning
confidence: 99%
“…Furthermore, tobacco exposure induces proinflammatory and immunosuppressive effects, which could potentially increase the likelihood of HPV infection and persistence 48,49 . Since risk factors such as smoking and alcohol consumption are strongly associated with sexual behaviour and are well established in the aetiology of HNSCC, this may confound the relationship between sexual behaviours with HPV transmission and similarly oropharyngeal cancer in observational studies 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many more variants related to alcohol use have been identified [81]. Using MR, Gormley et al confirmed that both alcohol and tobacco are independent risk factors for oral and oropharyngeal cancers with inverse variance weighted odds ratios of 2.1 and 2.6 respectively [82].…”
Section: Epidemiological Data Indicate a Strong Correlation Between Alcohol And Oral Malignanciesmentioning
confidence: 99%